Photon Versus Proton Beam Therapy for T1–3 Squamous Cell Carcinoma of the Thoracic Esophagus Without Lymph Node Metastasis - Suh, Yang-Gun; Bayasgalan, Unurjargal; Kim, Heung Tae; Lee, Jong Mog; Kim, Moon Soo; Lee, Youngjoo; Lee, Doo Yeul; Lee, Sung Uk; Kim, Tae Hyun; Moon, Sung Ho (Frontiers in Oncology, 2021)
Background and Purpose: We compared treatment outcomes and toxicities of photon radiotherapy versus proton beam therapy (PBT) and evaluated radiation field effects for T1-3 squamous cell carcinoma of the thoracic esophagus (EC) without lymph node metastasis. Methods: Medical records of 77 patients with T1-3N0M0 thoracic EC treated with radiotherapy between 2011 and 2019 were retrospectively analyzed. Among these patients, 61 (79.2%) individuals had T1 EC. The initial clinical target volume encompassed the whole esophagus with or without supraclavicular and/or abdominal lymph nodes (extended-field radiotherapy; 67 patients, 87.0%) or the area 3–5 cm craniocaudally and 1–2 cm radially from the gross tumor volume (involved-field radiotherapy; 10 patients, 13.0%). The final clinical target volume included margins of at least 1 cm from the gross tumor volume, with total radiation doses of 50–66 (median, 66) cobalt gray equivalent. Three-dimensional conformal radiotherapy, intensity-modulated radiotherapy, and PBT were used in 24, 5, and 48 patients, respectively. Concurrent chemotherapy was administered to 17 (22.0%) patients overall and only 5 (8.0%) T1 patients. Results: PBT showed significantly lower lung and heart radiation exposure in mean dose, V5, V10, V20, and V30 than photon radiotherapy. The median follow-up for all patients was 46 (interquartile range, 22–72) months. The 5-year progression-free survival and overall survival rates were 56.5% and 64.9%, respectively, with no significant survival difference between photon radiotherapy and PBT. In patients with T1 EC, 5-year progression-free survival and overall survival rates were 62.6% and 73.5%, respectively. Conclusions: Extended-field radiotherapy using modern radiotherapy techniques without chemotherapy showed satisfactory clinical outcomes for lymph node-negative T1 EC.